The Effect of Plant Additives on the Stability of Polyphenols in Cloudy and Clarified Juices from Black Chokeberry (Aronia melanocarpa) - Andrzej Sidor; Agnieszka Drożdżyńska; Anna Brzozowska; Artur Szwengiel; Anna Gramza-Michałowska (MDPI AG, 2020)
Black chokeberry (Aronia melanocarpa) is a fruit with increasing popularity in consumption and processing. Recent research has strengthened the position of chokeberry as a source of phenolic compounds, antioxidants with high pro-health values, therefore it is important to investigate other substances protecting biologically active compounds during juice processing. This study was an attempt to reduce the loss of polyphenol in cloudy and clarified chokeberry juice by adding aqueous cinnamon and clove extracts. The results showed that the clarification of juices did not cause significant changes in the concentration of polyphenols. However, the addition of plant extracts prior to pasteurisation process influenced the content of phenolic compounds in the chokeberry juices. The main change in the composition of the chokeberry juices observed during storage was a result of the degradation process of anthocyanins. The research showed that, despite the common view about the beneficial effects of polyphenols and other compounds exhibiting mutual antioxidative potential, it is very difficult to inhibit the degradation process.